Selective Adsorption and Photocatalytic Degradation of Dyes Using Polyoxometalate Hybrid Supported on Magnetic Activated Carbon Nanoparticles under Sunlight, Visible, and UV Irradiation - Mehdi Taghdiri (International Journal of Photoenergy)
In this study, magnetic activated carbon (MAC) nanoparticles were coated with an organic hybrid of silicotungstic acid that makes MAC suitable for adsorption and photocatalytic degradation of dyes. The prepared composite was characterized by Fourier transform infrared spectroscopy, powder X-ray diffraction, thermal analyses, scanning electron microscopy, vibrating sample magnetometer, and N2 adsorption-desorption isotherms. Dye adsorption and photocatalytic properties of composite were examined by studying the decolorization of model dyes methylene blue (MB), methyl orange (MO), rhodamine B (RhB), and their mixture solutions. The results show that the composite can selectively adsorb MB molecules from binary mixtures of MB/MO or MB/RhB, and its adsorption capacity is enhanced as compared with the MAC. The composite is also, unlike MAC, a good photocatalyst in the degradation of dyes under sunlight, visible, and UV irradiation and can be separated by magnet, recovered and reused. Removal is via combination of adsorption and then photocatalytic degradation through direct oxidation by composite or indirect oxidation by •OH radicals. While the sunlight is not able to degrade alone MO and RhB solution in the presence of composite, it degrades the MO and RhB mixed with MB solution.